2019
DOI: 10.1089/trgh.2018.0045
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Assessment of Selected Social Determinants of Health in a Sample of Transgender and Gender Nonconforming Individuals in Puerto Rico

Abstract: Purpose: Transgender and gender nonconforming (GNC) people continue to experience suboptimal health care, social exclusion, and lower quality of life. Globally, lack of access to services, institutional violence, and public harassment have been reported. However, there is limited data on transgender health in Puerto Rico and the Caribbean. The purpose of this study is to assess the social determinants of health and wellbeing of transgender and GNC people living in Puerto Rico.Methods: Utilizing a community-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 44 publications
0
30
0
2
Order By: Relevance
“…Although limited to a smaller sample size (n=59), we encountered similar findings in a study on the social determinants of health of transgender populations in Puerto Rico. 7 In this study, the main barrier to healthcare was the lack of knowledge from healthcare providers (59.6%). Study participants also identified discomfort in health encounters (55.8%) and provider discrimination (42.3%) as part of their experiences.…”
Section: Introductionmentioning
confidence: 69%
“…Although limited to a smaller sample size (n=59), we encountered similar findings in a study on the social determinants of health of transgender populations in Puerto Rico. 7 In this study, the main barrier to healthcare was the lack of knowledge from healthcare providers (59.6%). Study participants also identified discomfort in health encounters (55.8%) and provider discrimination (42.3%) as part of their experiences.…”
Section: Introductionmentioning
confidence: 69%
“…The TNB community experiences significant disparities across all determinants of health, including higher rates of homelessness, unemployment, and poverty. [14][15][16][17] Additionally, experiences of violence and victimization are frequent for TNB individuals and results in long-lasting effects on both the individual and the community. 15,18,19 According to the National Transgender Discrimination Survey, 40% of TNB people reported suicide attempts, as compared with 4.6% of the general population.…”
Section: A J P E a C C E P T E D D R A F T Tnb Health Disparitiesmentioning
confidence: 99%
“…As well, lesbians have been found to consult doctors less frequently than heterosexual women and report having fewer pap tests (Tjepkema, 2008 ). Transgender people, in particular, face unique barriers to accessing appropriate health care regarding reproductive health and transition surgeries (Bauer et al, 2009 ; Hudson, 2019 ; Institute of Gender & Health, 2012 ; Martinez-Velez et al, 2019 ). Access to appropriate sexual health education and resources for queer youth are also ongoing health equity concerns (Johns et al, 2019 ; McKenzie, 2015 ).…”
Section: Introductionmentioning
confidence: 99%